2019
DOI: 10.1101/gad.325241.119
|View full text |Cite
|
Sign up to set email alerts
|

Activator of one protease transforms into inhibitor of another in response to nutritional signals

Abstract: All cells use proteases to adjust protein amounts. Proteases maintain protein homeostasis by degrading nonfunctional toxic proteins and play regulatory roles by targeting particular substrates in response to specific signals. Here we address how cells tune protease specificity to nutritional signals. We report that Salmonella enterica increases the specificity of the broadly conserved proteases Lon and ClpSAP by transforming the Lon activator and substrate HspQ into an inhibitor of the N-degron recognin ClpS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 48 publications
0
22
1
Order By: Relevance
“…4 ). These features are commonly found in several bacterial AAA+ adaptor proteins including the bacterial N-recognin, ClpS, which modulates both the specificity and the stability of its cognate unfoldase (ClpA) both in vitro and in vivo 30 , 52 , 68 70 . Our structural and biochemical studies demonstrate that PDIP38 is composed of two domains that are joined by a hinge region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 ). These features are commonly found in several bacterial AAA+ adaptor proteins including the bacterial N-recognin, ClpS, which modulates both the specificity and the stability of its cognate unfoldase (ClpA) both in vitro and in vivo 30 , 52 , 68 70 . Our structural and biochemical studies demonstrate that PDIP38 is composed of two domains that are joined by a hinge region.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the absence of these substrates, HspQ is rapidly degraded by Lon 71 . Interestingly, under conditions of high acetyl-CoA, HspQ becomes acetylated and its turnover by Lon is inhibited 70 . This results in the accumulation of Ac-HspQ in the cell, which binds to ClpS and inhibits the turnover of N-degron substrates by ClpAP 70 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ClpA/C/X chaperones also recognize disordered regions ( 10 , 93 ) as substrates. Adding to the complexity of substrate recognition and selection is the notion that adaptor proteins not only bind and deliver substrates but also they can also modulate substrate selection of proteases, as exemplified by, for example, HspQ and ClpS, influencing the activity of both ClpAP and the Lon protease in Salmonella enterica ( 94 ). In this section, we review the current understanding of ClpS homologs found in cyanobacteria, plastids, and apicoplasts and insight in N-degrons.…”
Section: Clps Homologs and N-degrons Across Cyanobacteria Plastids mentioning
confidence: 99%
“…In a nutrient-deficient medium, phosphorylation inhibits the protease activity of Lon in Xanthomonas citri (Zhou et al, 2018). Post-translational modifications of Lon substrates may also explain the different functions of Lon in different media (Yeom and Groisman, 2019). In Salmonella enterica, the acetylation of HspQ in response to growth on glucose can block the degradation by Lon (Yeom and Groisman, 2019).…”
Section: Discussionmentioning
confidence: 99%